1995
DOI: 10.1007/bf02369379
|View full text |Cite
|
Sign up to set email alerts
|

Instability of a three-dimensional supersonic boundary layer

Abstract: 532.526The instability of three-dimensional boundary layers has become an area of intensive theoretical and experimental research in the last decade [1, 2]. Such boundary layers are encountered in particular in the flow of air past swept wings on aircraft in regions of negative and positive longitudinal pressure gradients.Nearly all of the studies have been conducted for subsonic flow velocities. However, despite the large volume of research, the problem is still not fully resolved: there are qualitative diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 5 publications
0
11
1
Order By: Relevance
“…The minimum of pU(z ~) near z r ~ 4.5-6.0 mm observed in all distributions is caused by a steady streamwise perturbation. Steady vortices in a three-dimensional boundary layer were observed in experiments [9][10][11][12]. In contrast to the results of these papers, the size of a steady perturbation obtained in our experiments is several times greater than the scale of cross-flow steady vortices.…”
contrasting
confidence: 78%
See 1 more Smart Citation
“…The minimum of pU(z ~) near z r ~ 4.5-6.0 mm observed in all distributions is caused by a steady streamwise perturbation. Steady vortices in a three-dimensional boundary layer were observed in experiments [9][10][11][12]. In contrast to the results of these papers, the size of a steady perturbation obtained in our experiments is several times greater than the scale of cross-flow steady vortices.…”
contrasting
confidence: 78%
“…King [10] concluded that crossflow vortices are less susceptible to acoustic disturbances than the fundamental-mode disturbances or Tollmien-Schlichting waves. Some results of numerical investigation of instability of a three-dimensional boundary layer for M = 3.5 are presented in [11].The first experimental studies of instability of a three-dimensional boundary layer at supersonic velocities were conducted in [12,13]. Evolution of natural fluctuations in the boundary layer on a swept wing was studied.…”
mentioning
confidence: 99%
“…The experiments [6] showed that the distribution of the mean and fluctuating characteristics in the boundary layer at supersonic velocities is the same as that at subsonic velocities. Natural fluctuations enhance in the downstream direction.…”
Section: Introductionmentioning
confidence: 84%
“…Experimental investigations of stability of three-dimensional supersonic boundary layers are now undertaken [6,9,10]. To analyze and interpret the experimental data, they have to be compared with the results calculated by the linear theory.…”
Section: Introductionmentioning
confidence: 99%
“…If the issues of stability of the laminar boundary layer at subsonic speeds were studied thoroughly in both experimental and theoretical papers [1,2], for supersonic speeds these problems are less investigated [1,[3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%